EDUCAŢIA ECOLOGICĂ PRIN ACTIVITĂŢILE DIDACTICE ŞI EXTRAŞCOLARE (PANGEEA, 2025)
Environmental education through the educational and extracurricular activities. The paper presents some aspects of environmental education in schools, emphasizing its importance in training students a realistic outlook on the world and life. In this context it stresses the need for disciplines that ensure the implementation of this goal to enjoy a realistic status.